On inequalities for seminorms of certain classes of differentiable periodic functions - Polyakov, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We obtained the inequalities for upper bounds of seminorms of classes of 2π-periodic functions, which are determined by a linear differential operator and by the majorant of the modulus of continuity.